A Critique of Beautiful News: Positive Trends, Uplifting Stats, Creative Solutions - Tate Caughman; Lacey Roberts-Hill (Journal of Applied Communications, 2025)
This book review is a critical evaluation of the David McCandless' book titled, Beautiful News: Positive Trends, Uplifting Stats, Creative Solutions. In this critique we summarize the essence of the written work and connect the work to the field of agricultural communications and applied practices. We offer some insights into contradictions we viewed from the perspective and expectations of data visualization strategies for communicating information. Finally, we recommend the book for those seeking inspiration for data visualization design and those needing a push to think outside the traditional strategies used in the field.
Keywords: data visualization; data storytelling; book review